PDAM TIRTA KEPRI SEBAGAI SANITASI DI WILAYAH DI KOTA TANJUNGPINANG - Sutrisno, Tri; Henry, OK (Jurnal Potensi, 2021)
Water is a basic human need that must be met every day. This results in the provision of water to be carried out even though the availability of raw water is limited. The limited availability of raw water is caused by the reduced water catchment area due to land conversion, the reservoir environment that has not been optimally conserved, and the reservoir as a reservoir for raw water which is not sufficient in number, even though the raw water in Tanjungpinang City comes from rainfall, so it is necessary to for the construction of a new reservoir. This research was conducted with the aim of knowing the management of resources by PDAM Tirta Kepri. This is because PDAM Tirta Kepri as a company engaged in the management, supply, and distribution of water to the community, thus has the responsibility to manage water resources. PDAM Tirta Kepri is a company that manages clean water which has been consumed by the people of Tanjungpinang. Even though it has been running so far, PDAM Tirta Kepri still needs to maximize the number of sales in order to meet the water needs of the people of Tanjungpinang city.